The impact of traffic congestion when optimising delivery routes in real time. A case study in Spain. Issue 5 (3rd September 2018) - Alvarez, Pablo; Lerga, Iosu; Serrano-Hernandez, Adrian; Faulin, Javier
ABSTRACT: This paper studies the importance of considering congestion costs when optimising delivery routes. Through the analysis of two study areas (the region of Catalonia and the city of Barcelona, in Spain), four different scenarios have been implemented and compared in which different objective functions are minimised: Euclidean distance, real distance, real time with static congestion, and real time with dynamic congestion. The data have been collected from Google Maps, which allows us to obtain information on traffic conditions in real time. The results indicate that minimising real time considering congestion as a dynamic attribute which varies throughout the day is the most efficient method to optimise delivery routes, especially within urban areas. For the two study areas, and using this dynamic approach in which real-time congestion costs are reflected into the vehicle routing problem, savings in time up to 11% have been obtained.